Responsibility of The Perpetrator in The Form of Compensation for The Unlawful Act of Fraud - Irene Princess AS Sinaga; Owen Gavriel Suherman; Nathanael's Star (Warmadewa Press, 2024)
Fraud is an act that is clearly against the law that has been regulated in the Unitary State of the Republic of Indonesia where fraud can cause losses to the Indonesian people. However, asking for compensation for fraud that has been committed by certain individuals is not an easy thing to do because fraud can enter the legal chamber and the civil chamber where the criminal court has the authority to impose penalties on the perpetrator in the form of fines and imprisonment, while the civil court has the authority to order the perpetrator to provide compensation to the victim. Although fraud can be addressed through civil proceedings to seek compensation, the research highlights that proving fraud is most effectively achieved in a criminal court. This underscores the necessity of obtaining an infract criminal decision one that is legally binding to establish the fraud. Such a decision serves as a prerequisite for ensuring that a civil claim for compensation is neither deemed premature nor rejected. The research recommends prioritizing criminal proceedings as a foundational step to strengthen civil compensation claims and ensure their admissibility.